Analisis Penerapan Klausul-Klausul Sistem Manajemen Lingkungan ISO 14001:2015 pada Pekerjaan Konstruksi di Proyek X - Imam Mubasyir; Wahyuni Susilowati; Jonathan Saputra (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2021)
Infrastructure development, according to the Strategic Plan of the Ministry of PUPR 2020-2024, is prioritized to support basic services, economic development, and urban development. The implementation of infrastructure development is strived to increase economic growth. However, non-compliance with quality standards is still a problem in infrastructure development. One of the quality standards that is often overlooked is the environmental management system to ensure environmental quality in construction projects. There is a need for environmental management on a project that runs according to the standards planned and the importance of implementing environmental management in the project. Therefore, a detailed study is needed in identifying and analyzing the implementation of the environmental management system and the constraints on its implementation in construction projects obtained by scientific questionnaire method and observation with contractor employees as internal parties and construction management consultant employees and owners as external parties in a construction project in Jakarta. The data were analyzed by using statistical tests with multiple linear regression, seeing its application in the field, and analyzing supporting documents. The clauses that are considered in the ISO 14001:2015 environmental management system are clauses 4-10. The results of the analysis show that clause 5 is the clause with the highest application effect with a regression coefficient of 0.967. Factors that become obstacles and need special attention in this project are clauses 4, 6, and 10.